STRUCTUSTRUCTURAL AND DYNAMIC FEATURES OF ACUTE PSYCHOSIS DUE TO THE USE OF SYNTHETIC CANNABINOIDSRAL AND DYNAMIC FEATURES OF ACUTE PSYCHOSIS DUE TO THE USE OF SYNTHETIC CANNABINOIDS - A.S. Subkhanberdina; T.V. Klimenko (Interdisciplinary Approaches to Medicine, 2020)
In the last 10 years, virtually all countries have faced a change in the structure of drug use due to a decrease in the number of opiate along with an increase in the number of users of the so-called “new” psy- choactive substances Upon data collection from 126 patients, a dynamic clinical study of 356 psychotic states due to the use of synthetic cannabinoids was undertaken. Consecutive stages of development of psychosis along with its delirious, oneiroic, and amentive-like clinical variants were identified.  The likelihood  of development of psychosis and its clinical variants is determined by a complex of clinical, biological, psychopathological, and socio-psychological factors.